Analisis Kemampuan Menulis Karya Tulis Ilmiah Mahasiswa Program Studi Pendidikan Teknologi Informasi STKIP Taman Siswa Bima - Ramdani Purnamasari (Medan Resource Center, 2023)
This qualitative field research aims to analyze students' writing skills in scientific writing. The data source comprises students from the Information Technology Education Study Program at STKIP Taman Siswa Bima, specifically those enrolled in Indonesian language courses during the odd semester of 2022/2023. The data collection method utilized tests, while data analysis followed the Miles and Huberman models. Findings indicate that students' writing skills scored an average of 72.3% across various aspects, including content of ideas (22.2%), organizational content (14.15%), grammar (14.2%), vocabulary (17.65%), and spelling/writing (4.1%). Overall, the study concludes that students' ability to write scientific papers in the Information Technology Education Study Program at STKIP Taman Siswa Bima is at a good level.